Impact of Capital Adequacy Ratio, Credit to Deposit Ratio, Dividend Policy and Ownership Structure in Financial Performance of Nepalese Commercial Banks - Sah, Khushbu (Campion Journal of Multidisciplinary Research and Explorer, 2026)
This study explores how various factors such as capital adequacy ratio, credit to deposit ratio, dividend policy, and ownership structure affect the profitability of Nepalese commercial banks. The dependent variables in this research are return on assets (ROA) and net interest margin (NIM), while the independent variables include capital adequacy ratio, credit to deposit ratio, dividend payout ratio, dividend yield ratio, foreign ownership, government ownership, and bank size. The study utilizes secondary data from 15 commercial banks, with 135 observations spanning the years 2015/16 to 2023/24. Data was gathered from the Banking and Financial Statistics published by Nepal Rastra Bank, along with annual reports and publications from respective commercial banks. Regression models and correlation coefficients were applied to assess the significance of these independent variables on the profitability of Nepalese banks. The findings indicate that factors such as capital adequacy ratio, credit to deposit ratio, dividend payout ratio, bank size, and government ownership are negatively related to the return on assets of Nepalese banks. This suggests that higher values in these variables lead to lower ROA. Conversely, foreign ownership and dividend yield have a positive impact on ROA. Additionally, the study finds a negative relationship between these factors (except government ownership) and net interest margin, meaning that higher values in these variables correspond to a lower NIM. However, government ownership was found to positively affect net interest margin.